Mechanisms of Sorafenib Resistance in HCC Culture Relate to the Impaired Membrane Expression of Organic Cation Transporter 1 (OCT1) - Chava S; Ekmen N; Ferraris P; Aydin Y; Moroz K; Wu T; Thung SN; Dash S (Journal of Hepatocellular Carcinoma, 2024)
Srinivas Chava,1 Nergiz Ekmen,2 Pauline Ferraris,1 Yucel Aydin,2 Krzysztof Moroz,1 Tong Wu,1 Swan N Thung,3 Srikanta Dash1,2,4 1Department of Pathology and Laboratory Medicine, Tulane University Health Sciences Center, New Orleans, LA, USA; 2Department of Gastroenterology and Hepatology, Tulane University Health Sciences Center, New Orleans, LA, USA; 3Department of Pathology, Icahn School of Medicine at Mount Sinai, New York, NY, USA; 4Southeast Louisiana Veterans Health Care System, New Orleans, LA, USACorrespondence: Srikanta Dash, Department of Pathology and Laboratory Medicine, Tulane University Health Sciences Center, 1430 Tulane Avenue, New Orleans, LA, 70112, USA, Tel +1 504-988-2519, Fax +1 504-988-7389, Email sdash@tulane.eduIntroduction: Sorafenib, an FDA-approved drug for advanced hepatocellular carcinoma (HCC) treatment, encounters resistance in many patients. Deciphering the mechanisms underlying sorafenib resistance is crucial for devising alternative strategies to overcome it.Aim: This study aimed to investigate sorafenib resistance mechanisms using a diverse panel of HCC cell lines.Methods: HCC cell lines were subjected to continuous sorafenib treatment, and stable cell lines (Huh 7.5 and Huh 7PX) exhibiting sustained growth in its presence were isolated. The investigation of drug resistance mechanisms involved a comparative analysis of drug-targeted signal transduction pathways (EGFR/RAF/MEK/ERK/Cyclin D), sorafenib uptake, and membrane expression of the drug uptake transporter.Results: HCC cell lines (Huh 7.5 and Huh 7PX) with a higher IC50 (10μM) displayed a more frequent development of sorafenib resistance compared to those with a lower IC50 (2– 4.8μM), indicating a potential impact of IC50 variation on initial treatment response. Our findings reveal that activated overexpression of Raf1 kinases and impaired sorafenib uptake, mediated by reduced membrane expression of organic cation transporter-1 (OCT1), contribute to sorafenib resistance in HCC cultures. Stable expression of the drug transporter OCT1 through cDNA transfection or adenoviral delivery of OCT1 mRNA increased sorafenib uptake and successfully overcame sorafenib resistance. Additionally, consistent with sorafenib resistance in HCC cultures, cirrhotic liver-associated human HCC tumors often exhibited impaired membrane expression of OCT1 and OCT3.Conclusion: Intrinsic differences among HCC cell clones, affecting sorafenib sensitivity at the expression level of Raf kinases, drug uptake, and OCT1 transporters, were identified. This study underscores the potential of HCC tumor targeted OCT1 expression to enhance sorafenib treatment response.Keywords: hepatocellular carcinoma, HCC, cholangiocarcinoma, CCA, tyrosine kinase inhibitors, TKI, organic cation transporter-1, OCT1, organic cation transporter-3, OCT3, sorafenib resistance cell lines, SR huh 7